2006
DOI: 10.1002/zaac.200600171
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of NbOBr2

Abstract: Black, needle shaped crystals of NbOBr 2 were formed by reduction of NbOBr 3 with InBr at 500°C. It crystallizes isotypically to NbOI 2 (monoclinic, space group C2, a ϭ 13.833(4), b ϭ 3.9079(6), c ϭ 7.023(2) Å , β ϭ 105.026(10)°). The structure consists of NbO 2 Br 4 octahedra, which are connected to layers 2 ϱ [NbO 2/2 Br 4/2 ]. Nb atoms of edge sharing octahedra form Nb 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 5 publications
2
8
0
Order By: Relevance
“…It was shown that the NbCl 4 O 2 octahedra are distorted by the formation of NbϪNb bonds and alternating NbϪO distances. This model was confirmed for NbOBr 2 by Beck et al [11]. In this case, too, single crystals were obtained as a by-product from the reaction of NbOBr 3 and InBr.…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…It was shown that the NbCl 4 O 2 octahedra are distorted by the formation of NbϪNb bonds and alternating NbϪO distances. This model was confirmed for NbOBr 2 by Beck et al [11]. In this case, too, single crystals were obtained as a by-product from the reaction of NbOBr 3 and InBr.…”
Section: Introductionsupporting
confidence: 71%
“…But the values of the displacement parameters and out-of-centre position of Nb are very similar to our results on NbOI 3 , so the model in C2 is probably correct. The non-centrosymmetric model (C2) with alternating NbϪNb and NbϪO distances was recently confirmed for NbOBr 2 [11].…”
Section: Comparison To Nbocl 3 and Further Oxidehalides With Chain Stmentioning
confidence: 71%
See 1 more Smart Citation
“…As determined by experimental structural characterizations, [29][30][31] bulk NbOX 2 can crystalize in a ferroelectric C2 phase with monoclinic symmetry, where Nb cations exhibit non-zero off-center displacement along the Nb-O-Nb atomic chain direction (b axis). In our work, in order to explore all possible NbOX 2 polar configurations, we choose the Nb polar-distortion free, centrosymmetric C2/m phase (ground state structures for MoOCl 2 34 and TaOI 2 35 ) as the paraelectric (PE) reference for bulk NbOX 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Bulk NbOX 2 have been synthesized since the 1960s, 27,28 and they can be potentially exfoliated into 2D layered forms. Despite their structural polarities at room temperature, [28][29][30][31] NbOX 2 have not been considered or investigated as 2D layered ferroelectrics. Except for earlier tight-binding band structure calculations, 32 accurate predictions regarding electronic and FE properties for NbOX 2 bulk and 2D layers have never been reported.…”
Section: Introductionmentioning
confidence: 99%